Prognostic value of Prognostic Nutritional Index in cancer: an umbrella review of systematic review and meta-analysis - Yang, Jiyu; Wang, Cuixue; Xue, Jian; Ma, Xiao; Hou, Yingze; Yuan, Haoran; Xia, Kaiyan; Piao, Long; Zhou, Xianchun (Frontiers in Nutrition, 2026)
BackgroundThe Prognostic Nutritional Index (PNI) is a critical biomarker reflecting the nutritional and immune status of cancer patients. Its association with the prognosis of various malignant tumors has been extensively investigated. However, a comprehensive systematic evaluation of the prognostic significance of PNI across different cancer types remains limited.MethodsThis umbrella review conducted a systematic search of PubMed, Embase, Web of Science, and the Cochrane Library to include meta-analyses that assessed survival outcomes related to cancer across diverse malignancy categories. The quality of the evidence was evaluated utilizing the GRADE and AMSTAR tools. Effect sizes, expressed as hazard ratios (HR) or odds ratios (OR), were synthesized using either random-effects or fixed-effects models. Additionally, analyses of heterogeneity, indicated by I2, and assessments of publication bias were performed as appropriate.ResultsThe Prognostic Nutritional Index (PNI) demonstrates associations across multiple cancer types, with a low PNI significantly linked to poor prognosis in 12 categories of malignant tumors. The HRs for 103 outcomes ranged from 1.15 to 2.98 (p < 0.05). The overall quality of evidence is predominantly low or very low, as assessed by the GRADE criteria, affecting 89.3% of outcomes. This is largely attributed to heterogeneity (47.8% with I2 > 50%), publication bias (40%), and limitations in AMSTAR scoring. Notably, 11 outcomes provided moderate-quality evidence, all indicating substantial effect sizes. Specifically, PNI shows significant prognostic value in breast cancer (preoperative overall survival [OS] HR = 2.56, postoperative HR = 2.63), cervical cancer (OS HR = 2.98), and among patients receiving immunotherapy (e.g., lung cancer immune checkpoint inhibitor [ICI] group OS HR = 2.68).ConclusionA low Prognostic Nutritional Index is consistently associated with poorer outcomes across various cancer types, particularly in predicting responses to immunotherapy. However, due to the current limited quality of evidence, it cannot yet be recommended as a standalone prognostic or decision-making tool across all tumors. Future rigorously designed, multi-center studies are required to validate its clinical utility.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/,CRD42025111093.